2018
DOI: 10.18182/tjf.320131
|View full text |Cite
|
Sign up to set email alerts
|

A research on work motivation of managers of forest products industry in düzce

Abstract: İşletmelerde çalışanların performanslarını arttırmaları istenen bir amaçken bu durum iş motivasyonu ile sağlanabilmektedir. İş motivasyonu konusunda genel kabul görmüş motive edici temel faktörler olsa bile toplumdan topluma, kişiden kişiye, işletmeden işletmeye değişen motivasyon araçlarından söz etmek mümkündür. Yapılan bu çalışma ile Düzce orman ürünleri sanayi işletme yöneticilerinin iş motivasyonları incelenmiştir. Çalışmada Mottaz tarafından geliştirilen ve literatürde geçerliliği çeşitli çalışmalarla is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…These results are consistent with findings of Hitka et al (2022). In a study by Gedik et al (2018), women exhibited higher work motivation than men. In contrast, Aydin and Ucuncu (2016) reported higher average motivation among men in their research.…”
Section: Independent Sample T-test Results On Motivation Levels and W...supporting
confidence: 91%
See 3 more Smart Citations
“…These results are consistent with findings of Hitka et al (2022). In a study by Gedik et al (2018), women exhibited higher work motivation than men. In contrast, Aydin and Ucuncu (2016) reported higher average motivation among men in their research.…”
Section: Independent Sample T-test Results On Motivation Levels and W...supporting
confidence: 91%
“…The work of Gedik et al (2018) highlights that individuals aged between 31 and 40 exhibit elevated levels of work motivation. Correspondingly, the research conducted by Turkoglu and Yurdakul (2017) revealed that those aged 46 to 45 tend to experience greater job satisfaction and demonstrate improved job performance.…”
Section: One-way Anova Results Of Levels Of Motivation and Work Life ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrinsic motivation tools are more effective than extrinsic motivation tools on employees' work motivation. The effect of motivator on motivation does not differ according to the age, education level, marital status, average income, and status in the business and work experience of the employees [12]. Employee empowerment, employee training and teamwork applications have significant effects positive on the motivation of employees in the higher education sector [13].…”
Section: Introductionmentioning
confidence: 98%